Identifying the characteristics of socially integrated mobile bully-victims using a mobile application - Jokazi, Nombulelo (Department of Information Systems, 2025)
The prevalence of mobile bully-victim behaviour is increasing on popular mobile social networks. Mobile bullying is a sub-type of cyberbullying committed using mobile technology. Mobile bully-victims are individuals who exhibit both bullying and victimisation behaviour. While there are different types of bully-victims, research on bullying has traditionally focused on marginalised bully-victims, rather than on socially integrated bully-victims, who appear to present a greater risk to young people. Socially integrated bully-victims form interpersonal relationships through social interactions, and in the process, are victimised, and bully their peers in retaliation. This bullying is becoming more prevalent, especially among university students in South Africa. This is worrisome as previous studies have linked this behaviour to negative outcomes, such as depression, anxiety, and suicidal tendencies. In addition, studies indicate that identifying socially integrated bully-victims can be challenging. Consequently, this group is not widely known, nor widely catered for by bullying prevention programmes. The objective of this study was to develop a mobile application that could be used to identify the characteristics of socially integrated bully-victims who use mobile technology. The focus on mobile technology and mobile technology users is important since this technology is utilised more by young people to conduct bullying, compared to other technologies. To achieve this goal, extensive literature reviews were conducted to identify the characteristics of socially integrated mobile bully-victims, and how these arise. This led to the development of an integrative framework using the five factor theory (FFT), and Bronfenbrenner's socio ecological model (SEM). The link between these theories is the developmental systems theory (DST), which explains the bi-directional relationship between individual characteristics and environmental influences. A conceptual model was derived from this integrative framework. This then guided the design, development, and assessment of the socially integrated mobile bully-victim (SIMBV) application. The researcher adopted pragmatism as her philosophical paradigm, and design science (DS) as her research strategy. DS provided the steps needed to develop a useful application. The SIMBV application was tested in two iterations involving undergraduate students at a university in the Western Cape province of South Africa. Forty-two out of 143 participants from the first iteration were found to possess the characteristics of socially integrated bully victims. These consisted predominantly of females and males between 18 and 19 years of age. The second iteration had 54 respondents, who possessed the characteristics of socially integrated mobile bully-victims. The findings from the cluster analysis indicate that individual characteristics and environmental factors shape the characteristics of socially integrated mobile bullying victims. The key characteristics of the studied SIMBVs in the South African context are retaliation, low agreeableness, openness, hostility, characteristic adoption, consciousness, popularity, prior victimisation and mobile bully-victim behaviour. The environmental factors on the other hand include peer norms, coercion by parents, exposure to violence and cultural expectations. In addition, SIMBVs were found to defend friends and others. This finding differs from earlier studies, which tend to report only negative characteristics of bully-victims. This study contributes to theory by developing a more comprehensive and integrated framework of socially integrated mobile bully-victims characteristics. This integrated framework and the conceptual model can be used to develop useful tools to mitigate bullying committed over mobile phones. Identifying and understanding SIMBVs is made easier for psychologists in higher education with the mobile application. SIMBVs felt free to share the depth of their experience since the mobile application features ensure anonymity, and the psychologist user can know the true characteristics of the SIMBV in real time. The application can enable the development of relevant policies and effective interventions for this group. The mobile app has educational material on mobile bullying that can be utilised by universities and schools to raise awareness about this phenomenon.